The Halloween parade : text and jacket art by - Wells, Rosemary (Wells, Rosemary. Yoko and friends-- school days., 2001)
Yoko and Timothy aren't very frightening in their costumes that look like food, but they can still scare Doris and Stumpy, who ride an almost-real motorcycle in the school's Halloween parade.